Challenges to State Policy Capacity
IX, 287 p.
Keywords: Globalization and New Public Management pose major challenges to the policy capacity of the state. Challenges to State Policy Capacity offers the most timely and comprehensive coverage of contemporary state policy capacity. Drawing on the work by international leading scholars in political science and public administration, the book is indispensable to anyone interested in policy capacity, administrative reform and the state.